The Relationship Between Work Environment, Occupational Safety and Health Implementation, and Employee Performance: A Cross-Sectional Study - Simarmata, Vidi Posdo A.; Marantuan, Randolph Serep; Hutagalung, Patar (Journal of Applied Nursing and Health, 2025)
Background: A safe and comfortable work environment, along with effective OHS implementation, is essential for maintaining healthcare personnel productivity and performance; however, studies on the combined effect of both on employee performance in community health centers remain limited. At the same time, inadequate facilities, inconsistent procedural compliance, and minimal OHS socialization continue to hinder optimal service delivery. This study aims to analyze the relationship between the work environment and OHS implementation on employee performance at the East Bogor Community Health Center. Methods: A quantitative, correlational analytical design was employed, involving all 51 employees of the East Bogor Community Health Center as the total population sample. Data were collected through a structured and validated questionnaire, which was tested for reliability using Cronbach’s alpha (α > 0.80). The questionnaire measured three primary variables: work environment, OHS implementation, and employee performance. Data were analyzed using Pearson correlation and multiple linear regression at a 95% confidence level, following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines.. Results: The findings revealed a positive and statistically significant relationship between the work environment and employee performance (p = 0.012; r = 0.412, indicating a moderate correlation), as well as between OHS implementation and employee performance (p = 0.008; r = 0.436, also moderate). Together, both variables explained 38% of the variance in employee performance (R² = 0.38), suggesting that improvements in environmental and safety management factors can meaningfully enhance staff outcomes. Conclusion: A conducive work environment and sound OHS implementation jointly contribute to improved employee performance at the East Bogor Community Health Center. Management is recommended to strengthen OHS policies, improve work facilities, and enhance safety training to support optimal performance among healthcare workers.